Journal of software engineering research and development - Sociedade Brasileira de Computação (Springer, 2013)
"The aim of the Journal of Software Engineering Research and Development (JSERD) is to inform the readers about state of the art of software engineering by publishing high quality papers that represent results of consolidated research and innovations in software engineering and related areas."
Keywords: Software engineering : Periodicals; Computer software : Development : Periodicals; Computer software : Development; Software engineering